Two Instances of Language Contact in Isaiah 45:14. (23rd August 2019) - Boyd, Samuel
Abstract: Scholars have identified two traces of loans originating from Aramaic and Akkadian in Isa. 45:14. In this article, I examine each of the proposed borrowings, offering further support for the first, but arguing for a different path from Aramaic into the Hebrew of Isa. 45:14 for the second. In doing so, I add precision to the loan phonology of the lexeme as it relates to the sibilants involved and I call into question comparative evidence cited in Ludwig K.hler and Walter Baumgartner's The Hebrew and Aramaic Lexicon of the Old Testament .